Evaluation of toxic effects of dapagliflozin on reproductive system in diabetic rats - ERCAN, FERİHA (My University, 2022)
Background/aim: Dapagliflozin (DAPA), sodium-glucose cotransporter 2 (SGLT2) inhibitor, is an insulin-independent antidiabetic drug used to control hyperglycaemia by promoting glucose excretion from the kidney. Its adverse effects include orthostatic hypotension, dehydration and urinary tract and genital infections caused by glycosuria. DAPA is subjected to constant additional monitoring, as drug-related adverse reactions are frequently updated in line with the results of case studies, clinical trials and in vivo studies. Some antidiabetic drugs have shown potential harmful effects on the male reproductive system; however, the effects of DAPA have not been sufficiently studied in this capacity. Aiming to fill this gap in the literature, the present work investigates the toxic effects of DAPA on the male reproductive system.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Type-2 diabetes; dapagliflozin; male reproductive system; oxidative damage; GLUCOSE COTRANSPORTER 2; OXIDATIVE STRESS; MALE-FERTILITY; CHRONIC SAFETY; INHIBITOR; MELLITUS; PARAMETERS; MORPHOLOGY; APOPTOSIS; SPERM; Type-2 diabetes; dapagliflozin; male reproductive system; oxidative damage